Medicamentos genéricos: repercussões das patentes farmacêuticas na política de medicamentos - Wandscheer, Lucelaine dos Santos Weiss (2017)
The scope and limits of patent protection for pharmaceutical products and processes have aroused much debate. Therefore, clear rules on intellectual property are fundamental, as the effects of the misuse of patents in the pharmaceutical field have repercussions on access to medicines, as evidenced by this work. Generic drugs are generally produced after the expiration of the patent term of the reference drug, and constitute an effective public policy. Promoting access to innovative medicines and other medical technologies at affordable costs to a larger portion of the population has been a public health concern. The issue is related to intellectual property rules, especially after the TRIPS Agreement, and the implementation of these rules by the Member States of the World Trade Organization (WTO). As a result of the research we identified at least two strategies used in the pharmaceutical field. The first one is called second uses, and the second data protection test. These strategies are responsible for extending patent protection for pharmaceutical products and processes, with clear detriment to the National Medicines Policy. The basis of this research is composed of themes with strong interdisciplinary links.